Influence of corporate social responsibility in the institutional image of the financial institutions of Tacna, year 2017. - Hidalgo Aguilar, Omar Julinho (2019)
The main objective of this research work is to determine the extent to which corporate social responsibility influences the institutional image perceived by customers of Tacna financial institutions, year 2017. Study Basic and correlational type, non-experimental design. The sample consisted of 381 clients from financial institutions: Banco de Crédito del Perú, BBVA Continental, Scotiabank and Interbank. It was found that corporate social responsibility influences the institutional image perceived by clients (p = 0.010); the economic balance does not influence the institutional image perceived by clients (p = 0.209); the social balance influences the institutional image perceived by clients (p = 0.048); and the environmental balance does not influence the institutional image perceived by clients (p = 0.749). 57.9% of the clients consider that the corporate social responsibility they receive from Tacna financial institutions is of a regular level, and 61.2% of the clients consider that the institutional image they receive from the entities is of a regular level.